2011
DOI: 10.1007/s11357-011-9255-z
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal determinants and effect of ER22/23EK glucocorticoid receptor gene polymorphism on health status deterioration in the participants of the Mataró Ageing Study

Abstract: The purpose of this study is to assess the potential relationships of circulating IGF-I, adrenal and gonadal steroids, and polymorphism ER22/23EK of the glucocorticoid receptor (GC-R) gene with nutritional, functional and cognitive deterioration in a group of elderly people living independently. This is a population-based prospective study with 313 individuals (160 women and 153 men, 76.7±7 years) who participated. A physical exam, evaluation of functional capacity (Barthel scale), cognitive function (miniment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Our results showed little evidence of an association between morning cortisol and cognitive performance, in agreement with some of the literature 12 , 13 ; however, several studies have shown that higher morning cortisol is associated with worse cognitive performance (e.g. 11 , 35 ; Fig. S1a ; LASA cohort).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results showed little evidence of an association between morning cortisol and cognitive performance, in agreement with some of the literature 12 , 13 ; however, several studies have shown that higher morning cortisol is associated with worse cognitive performance (e.g. 11 , 35 ; Fig. S1a ; LASA cohort).…”
Section: Discussionsupporting
confidence: 92%
“…31 1140 women and men 50–70 yearssaliva 4 times over dayLanguage, executive function Verbal/visual memory, speedarea under the curve cross-sectionalMora et al . 35 313 women and men 76.7 ± 7SD yearsmorning serumMMSE Baseline and at 2 years follow-upHigher morning cortisol (women) cross-sectionalO’ Hara et al . 14 154 women and men 60–100 yearssaliva 5 times over dayMMSE, speed, spatial verbal memoryflatter diurnal drop cross-sectionalSchrijvers et al .…”
Section: Resultsmentioning
confidence: 99%
“…As previous studies have demonstrated that development of frailty over time is higher in women (Mora et al 2012b), we were interested in studying the role of obestatin in women's ageing. The purpose of the present study was to investigate if obestatin circulating concentrations are related to ageing phenotype in a cohort of non-institutionalized old women at baseline and after 2-year follow-up period.…”
mentioning
confidence: 99%
“…In men, mortality showed a trend to association with cortisol, cortisol/DHEA and association with cortisol/DHEAs ratio, while in women, mortality was associated to DHEA and cortisol/DHEA ratio. A previous study of our group observed a significant relationship between DHEA and testosterone with frailty development in men, but not in women . DHEA and DHEAs concentrations and its association to mortality in old people is a matter of substantial controversy.…”
Section: Discussionmentioning
confidence: 92%
“…A previous study of our group observed a significant relationship between DHEA and testosterone with frailty development in men, but not in women. 33 DHEA and DHEAs concentrations and its association to mortality in old people is a matter of substantial controversy. In the Swedish Men study, 16 and in another study, 34 both low DHEA and DHEAs predicted increased mortality only below 75 years of age but not above, while other two cohort studies have shown an association between low DHEAs and increased mortality in old men, 8,35 and finally, other six prospective studies indicate an association between lower DHEAs levels and atherosclerotic disease progression both in men and women, 36,37 but without demonstrating an association with mortality in women 35,38,39 and men.…”
Section: Discussionmentioning
confidence: 99%